2021
DOI: 10.4103/jfmpc.jfmpc_2433_20
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical presentation of sinusitis in pediatric age group in Aseer, Saudi Arabia

Abstract: Background: Paediatric rhinosinusitis is mostly different than that in adults. More frequently, children presented with cough, bad breath, crankiness, low energy, and swelling around the eyes, besides a thick yellow-green nasal or post-nasal discharge. About 5- 13% of childhood viral upper respiratory tract infections may advance to acute rhinosinusitis, with some of them developing a chronic condition. Aim: To assess prevalence and clinical presentation of sinusitis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
5
1
Order By: Relevance
“…(P=0.424) According to our findings, nasal obstruction was the most prevalent presenting symptom (33.3%), followed by fever, face pain, and rhinorrhea (22.2 %). The least reported symptoms in this study were nasal discharge and difficulty breathing [10]. Only one patient (11.11 %) had facial swelling, which has previously been found to be strongly indicative of acute invasive fungal rhinosinusitis (AIFR) [4], yet none of the patient in this study developed AIFR.…”
Section: Discussionmentioning
confidence: 60%
“…(P=0.424) According to our findings, nasal obstruction was the most prevalent presenting symptom (33.3%), followed by fever, face pain, and rhinorrhea (22.2 %). The least reported symptoms in this study were nasal discharge and difficulty breathing [10]. Only one patient (11.11 %) had facial swelling, which has previously been found to be strongly indicative of acute invasive fungal rhinosinusitis (AIFR) [4], yet none of the patient in this study developed AIFR.…”
Section: Discussionmentioning
confidence: 60%
“…Gilani et al showed that children in the age group of 5 to 15-year-old are more likely to be affected by RS ( 13 ). Chronic RS is common disease in children at different ages ( 15 ) and affects both children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In Saudi Arabia, studies regarding the prevalence and clinical presentation of RS in pediatric patients are scarce. A study done in Aseer reported that 30 patients out of the 100 patients included had a previous history of RS with 38% having a positive family history [13]. It is worth noting that this is the only study that has been conducted thus far, addressing the issue of sinusitis in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 97%